Assessing DANANTARA's Alignment with the Santiago Principles: Indonesia's Sovereign Wealth Fund Legal Regime in Comparative Perspective - Dharmma Justitio Hermawan; Prita Amalia; Purnama Trisnamansyah (Faculty of Law, University of Mataram, 2026)
This article examines the alignment of Indonesia’s newly established sovereign wealth fund, Daya Anagata Nusantara (Danantara), with the Santiago Principles on the global best-practice standards for sovereign wealth funds (SWFs). Danantara was created by Law No. 1 of 2025 (Third Amendment to the SOE Law) and subsequently governed under Law No. 16 of 2025 (Fourth Amendment) as a transformative vehicle to manage key state-owned assets, raising questions about its governance, transparency, and adherence to international norms. This study situates Danantara’s legal and institutional framework against the Santiago Principles’ guidelines, analyzing convergences, gaps, and challenges. It first clarifies the Santiago Principles’ content, legal status as soft law, and persuasive force in guiding SWF behavior globally. It then details Indonesia’s SWF architecture post-2025, highlighting Danantara’s objectives, structure, and regulatory provisions. The core analysis compares Danantara’s governance and operations with Santiago Principle benchmarks, revealing areas of harmony (such as a clear legal basis and objectives) and divergence (notably in independent oversight and transparency). A comparative discussion draws lessons from renowned SWFs: Temasek (Singapore) and Norway’s Government Pension Fund Global (GPFG) to contextualize Danantara’s approach. The article finds that while Danantara’s establishment represents a bold shift aligning in part with global best practices, critical improvements are needed to fully realize the Santiago Principles, especially in insulating the fund from political influence and enhancing accountability. The conclusion offers recommendations for strengthening Danantara’s governance and suggests that harmonizing with the Santiago Principles is vital for building credibility, attracting investment, and ensuring the fund’s long-term success.